Drastic sex-dependent etiological distribution in severe liver diseases from Gabon - Moussavou-Boundzanga, Pamela; Itoudi Bignoumba, Patrice Emery; Mouinga-Ondeme, Augustin; Iroungou, Berthe Amelie; Bivigou-Mboumba, Berthold; Marchio, Agnès; Saibou, Maryam; Moussavou Kombila, Jean-Baptiste; Pineau, Pascal (Frontiers in Oncology, 2022)
Chronic liver diseases still represent a worrying public health issue in Sub-Saharan Africa. In this region, emphasis is generally made on hepatocellular carcinoma (HCC) albeit liver cirrhosis (LC) is also responsible for an important death toll. Very few studies have compared the presentation and etiologies of cancer and cirrhosis of the liver in Middle Africa. We conducted a comparative retrospective analysis of 74 and 134 cases of patients with HCC and LC treated in Libreville, Gabon. Viral or lifestyle risk factors, clinical symptoms, and biological features were compared. We observed that ages of diagnosis were 53.2 ± 15.7 years and 48.6 ± 18.6 years for HCC and LC with remarkably low M:F sex ratios (1.3–1.8). Ethanol consumption was highly prevalent in both disease types (65.0%–70.0%). Chronic viral infections with hepatitis B (HBV) or C (HCV) virus were also widespread with slight domination of the former in both diseases (43.4% vs. 34.3%, and 35.9% vs. 28.5%). Patients with HCC were presenting very late with a mean diameter of the main nodule of 84 ± 50 mm and a multifocal pattern in 72.7% of cases. HCC developed on a cirrhotic liver in 91.7% of cases. Serum AFP was frankly elevated (>400 ng/ml) in only 35.8% of HCC cases. The most striking feature of the HCC series was the contrasted contribution of distinct pathogenic etiologies involving sex, viral, metabolic, and toxic factors. A frequently dysmetabolic condition synergizing with hepatitis C (anti-HCV, 73.8% vs 22.7%, p < 0.0001) in females and a male cancer promoted by recreational toxicants and chronic hepatitis B (HBsAg, 83.5% vs 35.9%, p < 0.0001) were observed. Men with HCC were considerably younger than women (46.8 ± 14.5 years vs. 62.2 ± 12.2 years, p < 0.0001). Further studies are now warranted to identify routes of HCV transmission and if they are still fueling reservoirs of future patients. Public policies to prevent alcohol-related harm have also to be urgently implemented in Gabon.